Eligibility and Exclusion of Hemochromatosis Patients as Voluntary Blood Donors. (1st February 1998) - Levstik, M; Adams, PC
Abstract : BACKGROUND: Hereditary hemochromatosis patients are excluded in many countries as voluntary blood donors. In 1991, changes in the Canadian Red Cross policy allowed healthy hemochromatosis patients to become voluntary donors. STUDY DESIGN AND METHODS: The medical histories of 208 hemochromatosis patients were evaluated for eligibility for blood donation from a large prospective database of hemochromatosis patients. A survey that determined the success or exclusion of 81 patients for blood donation and the reasons for their exclusion based on Canadian Red Cross donor exclusion criteria was analyzed. RESULTS: Of 208 hemochromatosis patients, 140 (67%) were eligible for blood donation. Criteria for exclusion were other illnesses excluded by Canadian Red Cross criteria and the use of contraindicated medications. Fifty-one per cent of patients had attempted to donate blood, with only 7% being successful. CONCLUSIONS: A large number of potential blood donors are excluded from blood donation inappropriately despite changes in eligibility criteria to the contrary. Further public and health education is needed to increase awareness and, thus, increase blood donation by potential donors.